Pelatihan Rehabilitasi Gerak Pasca Cedera Ringan pada Komunitas Senam Ibu-Ibu Ceria Desa Tupa - Parengkuan, Meyke; Mile, Rifky (-, 2025)
Minor injuries such as sprains and muscle soreness are common issues experienced by members of exercise communities, especially among adults. Limited knowledge regarding first-aid treatment and movement rehabilitation techniques often results in suboptimal recovery. This community service program aimed to improve the understanding and skills of the “Ibu-Ibu Ceria” exercise community in Tupa Village in recognizing and handling minor injuries independently. The training used a participatory approach involving lectures, simulations, and hands-on practice. Pretest results showed an average score of 52.1, which increased to 83.2 after the training. Additionally, 85% of participants were able to independently perform basic rehabilitation techniques. These results indicate that community-based training is effective in enhancing injury literacy and basic rehabilitative skills. It is expected that this program can serve as an educational intervention model for other active community groups.